The Archivists of “Information Age”: Interdisciplinary Travelers - Torunlar, Mehmet; Özdemirci, Fahrettin (Information World, 2014)
Developing technology in the world has also changed the necessities of information age and the quality of the archiving job and the archivist. Today, it is not possible to define science of archive with only one layer, to gather it in an auxiliary field under any discipline and to restrict it with only one discipline. In consideration of this age, archivist/records manager is an interdisciplinary traveler. Practises of public and private lives and dynamics of the information society indicate that archiving is an important discipline by itself rather than being an auxiliary field. A world without archives can be compared with audiences who cannot understand, know, see, and hear. Archives are not the documents which are no more in circulation, but indispensable functional parts of every field in the modern global life depended on information management such as prosperity, privacy, security, and personal rights. The managers should understand that archiving does not mean filing and storing the records and getting them out from the archives when they want. Archivists should know that archive/information-records management is a multi-layer scientific discipline consisting of applications, concern and activity fields of various scientific disciplines, and it is necessary for each science field in conducting scientific, personal, institutional, social and governmental activities in every society. In this study, a list of the books, which are regarded as useful in improving themselves for archivists/information-records managers, is presented by attracting attention to the interdisciplinary dimension of the science of archive.
Keywords: Archives; archivists; records management; records manager; archival information analysis; multiple realities